Comparison of histopathological features, survival, and oncological outcome between patients under and above 55-year-old with prostate cancer who underwent radical prostatectomy. Issue 1 (February 2023) - Soltani, Mohammad Hossein; Khabazian, Reza; Dadpour, Mehdi; Borumandnia, Nasrin; Simforoosh, Nasser
Background: To compare the disease course, histopathological features and survival rates of prostate cancer (PCa) between patients aged ⩽ 55 and > 55 year old. Materials and methods: In this retrospective study, we enrolled 644 patients with organ-confide prostate cancer who had undergone radical prostatectomy from 2005 to 2018. Seventy-six (11.8%) patients were under 55 years of age (group 1) and 568 (88.2%) patients were >55 years old (group 2). Results: Pre-operative hypertension was detected in 4 (5.3%) patients of group 1 and 80 (14.1%) patients of groups 2 ( p  = 0.029). The mean (±SD) prostate volume was higher in group 2 compared with group 1 (34.1(±8.4) ml vs 54.1(±9.9) ml, p  < 0.001). Positive surgery margin was observed in 15 (19.7%) and 58 (10.2%) patients in group 1 and 2, respectively ( p  = 0.020). Co-existence of diabetes mellitus, mean pre-operative PSA, Gleason's score, and permanent pathology and pathologic stage were similar between the two groups. Log-rank test failed to show any statistical difference in terms of biochemical-relapse free survival, local recurrence-free survival, and metastasis-free survival between the two groups ( p  = 0.316, 0.441, 0.654, respectively). After performing multivariate analysis, positive surgical margin was the only factor that was independently predictive of biochemical relapse ( p  < 0.001) and local recurrence/metastasis ( p  < 0.001). Conclusion: No difference was observed in terms of histopathologic features, biochemical relapse, and local recurrence/metastasis-free survival rates between patients younger and older than 55 years of age.